Analisis Efektivitas Penerapan Pasal 36 Ayat 3 Undang Undang No 32 Tahun 2002 tentang Penyiaran Terhadap Pemirsa Anak - Hadi, Adi Moh Kurnia; Heliany, Ina (Neolectura, 2025)
Television remains one of the main media for entertainment and information in Indonesia, even though digital media and streaming platforms are now increasingly developing. Watching television is a common activity among families, especially as a moment of togetherness after activities. However, along with the variety of shows provided by television stations, concerns have arisen regarding content that is not suitable for children. Shows that contain elements of violence, lies, slander, harassment, and even sensitive issues such as SARA and LGBT have the potential to damage children's psychological and social development. Therefore, it is important for parents to be more selective in controlling the shows their children consume. This research aims to evaluate the effectiveness of the implementation of Article 36 paragraph 3 of Law Number 32 of 2002 concerning Broadcasting in protecting children's broadcasts and how supervision and sanctions are applied to television stations that violate these provisions. This research uses qualitative normative legal research methods, with a focus on literature study and visual documentation analysis that utilizes primary, secondary and tertiary legal materials. The research results show that there are gaps in supervision and law enforcement regarding the broadcasting of children's shows in accordance with existing regulations. It is hoped that this research can provide input in developing broadcasting policies that are more effective and fairer for child protection in Indonesia.